Knowledge, Attitudes, and Beliefs about Relapse Prevention Research Involving Bupropion among Current and Former Pregnant Individuals Who Smoke. (16th December 2022) - Adkins-Hempel, Melissa; Japuntich, Sandra J.; Thomas, Janet; Fang, Pearl; Harrison, Katherine; Emery Tavernier, Rebecca L.; Winickoff, Jonathan P.; Kotlyar, Michael; Allen, Sharon
Abstract : Introduction . While many individuals quit smoking during pregnancy, most relapse within one year postpartum. Research into methods to decrease smoking relapse postpartum has been hampered by difficulties with recruitment. Method . We conducted individual interviews with pregnant women (N = 22 ) who were interested in quitting smoking while pregnant about their attitudes regarding smoking and quitting during pregnancy, clinical trial participation, and smoking cessation medication use. Results . Participants were aware of the risks of smoking while pregnant. Many wanted to quit smoking before delivery. Few used empirically supported treatments to quit. While research was viewed positively, interest in taking on new commitments postpartum and taking a medication to prevent relapse was low. Medication concerns were evident among most participants, especially among those planning to breastfeed. Further, several women noted medication was unnecessary, as they did not believe they would relapse postpartum. Financial incentives, childcare, and fewer and/or remote visits were identified as facilitators to participating in research. However, these factors did not outweigh women's concerns about medication use and time commitments. Conclusions . Women are aware that quitting smoking during pregnancy and remaining smoke-free postpartum are important. However, beliefs that personal relapse risk is low and that medications are dangerous reduced enthusiasm for taking medication for postpartum relapse prevention. Future medication trials should educate women about the high likelihood of relapse, prepare to answer detailed questions about risks of cessation medications, and connect with participants' clinicians. For new mothers, studies conducted remotely with few scheduled appointments would reduce barriers to participation.